Multi‐trophic β‐diversity mediates the effect of environmental gradients on the turnover of multiple ecosystem functions. (12th July 2019) - Martinez‐Almoyna, Camille; Thuiller, Wilfried; Chalmandrier, Loïc; Ohlmann, Marc; Foulquier, Arnaud; Clément, Jean‐Christophe; Zinger, Lucie; Münkemüller, Tamara
Abstract: Much effort has been devoted to better understanding the effects of environment and biodiversity on ecosystem functioning. However, few studies have moved beyond measuring biodiversity as species richness of a single group and/or focusing on a single ecosystem function. While there is a growing recognition that along environmental gradients, the compositional turnover of multiple trophic groups influences not only productivity but multiple ecosystem functions, we do not know yet which components of multi‐trophic β‐diversity influence which ecosystem functions. Here, we captured the biodiversity found in soils using environmental DNA to study total soil multi‐trophic β‐diversity (between all taxa regardless of their trophic group association), horizontal β‐diversities (β‐diversities within trophic groups) and vertical β‐diversity (β‐diversity across trophic groups) along a 1, 000 m elevational gradient in the French Alps. Using path analyses, we quantified how these β‐diversity components mediate the effects of environmental turnover on the turnover of multiple ecosystem functions (i.e. productivity, N‐cycling, N‐leaching) and overall multifunctionality. While we found a strong direct effect of soil properties on the turnover of multiple ecosystem functions, we also found an indirect effect of climate and soil properties through multi‐trophic β‐diversity. More specifically, only total multi‐trophic β‐diversity and the horizontal β‐diversity of saprophytic fungi were strongly related to the turnover of multifunctionality and, to a lower extent, the turnover of productivity and N‐cycling. Our results suggest that decomposition processes and resulting nutrient availability are key to understand how ecosystem functions change along soil properties and climatic gradients in alpine ecosystems. By demonstrating how saprophytic fungi and their associated trophic groups can offset the direct responses of multiple ecosystem functions to environmental change, our study highlights the paramount importance of multi‐trophic diversity for better understanding ecosystem multifunctionality in a changing world. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.